QUALIDADE DE QUEIJO TIPO CAMEMBERT:CULTURAS PRIMÁRIAS E INÓCULO DE MICÉLIO MICROFRAGMENTADO - Judacewski, Priscila (2015)
The Camembert is considered one of the finest cheeses. Presents as main characteristic the surface covered with a white mycelium of the fungus Penicillium candidum, which provides peculiar sensory characteristics greatly appreciated. In Brazil, little has been studied about this cheese, in this way, in order to generate scientific technical knowledge about factors that may influence the standard of quality cheeses such as Camembert, this work was divided into two parts. In the first (Chapter II), the objective was to evaluate the application of different primary cultures, and different concentrations of salt in the curing process. In the second (Chapter III), the objective was to develop and evaluate a protocol for obtaining fresh biomass of Penicillium candidum for use as a catch crop. Were used as primary cultures mesophilic homofermentative, heterofermentative mesophilic and thermophilic. The concentration of the brine used was 15, 20, 25 and 29º Brix. The biomass of P. candidum obtained in synthetic medium was recovered, and micro fragmented sprayed onto cheeses, with score of 2.106 spores / cheese. Of physical and chemical composition analyzes were performed, maturation index, colorimetric analysis and texture profile in the samples during maturation. The mycelia growth was established by the whiteness index (WI), which proved effective for this purpose, it is fast and inexpensive. Although the texture profile parameters were similar during maturation with different primary cultures, resilience showed lower value for processed cheeses with thermophilic culture, and was the only parameter that showed significant differences between cultures. Another positive factor for cheeses with this culture was superficial development of white mold mycelium with one-day gain, compared to mesophilic. Samples with different salt concentrations, showed significant differences (p <0.05) between the moisture, protein, dry matter, ash, sodium and sodium chloride, and did not affect the growth of the fungus P. candidum. The physical and chemical composition of cheeses matured with biomass was similar to cheeses matured with spores, but proteolysis of cheeses matured with biomass was more intense, with the end of 15 days of aging, free amino acid content of 14% more, compared with samples containing only spores. Among the samples with the application of the inoculums, the tyrosine levels and fat, as well as the cohesiveness of the texture profile parameter showed significant difference. The mycelium overlaid cheese with a day in advance when compared only with the inoculums of spores and showed greater height. This work demonstrates ways to monitor and speed up the mycelium closing within two days, using colorimetric analysis, thermophilic culture and micro fragmented biomass. These results can be readily used by companies to establish quality standards for cheese like Camembert.